Re-addressing resilience in communities facing the covid19 pandemic: an overview on coworking spaces in central european peripheries - Lukáš Danko; Gislene Feiten Haubrich; Eva Belvončíková (Netcom)
Sharing spaces signify the idea of developing permanent and temporary workspaces, which tend to provide innovation activities through communities in the “fourth” place. The engagement of stakeholders in local communities likewise increases the group cohesion and resilience of the local creative ecosystem. However, research on CWS and resilience/adaptability is scarce, especially concerning coping mechanisms with the Covid19 pandemic. The paper aims to identify what challenges CWS from Central European countries faced during the Covid19 pandemic and understand how they reinvented practices to support resilience in the community-organisation-space nexus. Our qualitative analysis, based on interviews with community managers, suggests CWS in peripheries could attract and sustain a diversity of stakeholders with physical and virtual spaces to collaborate, enhancing the resilience of communities. On the other hand, it means increased pressure on community managers to provide infrastructure for the hybridization of collaborative spaces along with adaptability to cover new demands (HR development and infrastructure).